2020
DOI: 10.1093/mnras/staa3035
|View full text |Cite
|
Sign up to set email alerts
|

On the accretion history of galaxy clusters: temporal and spatial distribution

Abstract: We analyse the results of an Eulerian AMR cosmological simulation in order to quantify the mass growth of galaxy clusters, exploring the differences between dark matter and baryons. We have determined the mass assembly histories (MAHs) of each of the mass components and computed several proxies for the instantaneous mass accretion rate (MAR). The mass growth of both components is clearly dominated by the contribution of major mergers, but high MARs can also occur during smooth accretion periods. We explored th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 62 publications
1
29
0
Order By: Relevance
“…As presented in Schneider & Bartelmann (1997) show that the dominant azimuthal order is the quadrupole m = 2 (see also Vallés-Pérez et al 2020) and the second most significant azimuthal symmetric orders are m = 1, 3, 4 with contributions higher than 10% (see also Gouin et al 2020). In details, the azimuthal matter distribution inside galaxy clusters (up to R 200 ) is almost quadrupolar, whereas the matter distribution in cluster infalling regions (from R 200 to 4 × R 200 ) is mainly traced by the harmonic orders m = 1, 2, 3, 4.…”
Section: Appendix A: Multipolar Expansion Of Dm Distributionmentioning
confidence: 90%
See 1 more Smart Citation
“…As presented in Schneider & Bartelmann (1997) show that the dominant azimuthal order is the quadrupole m = 2 (see also Vallés-Pérez et al 2020) and the second most significant azimuthal symmetric orders are m = 1, 3, 4 with contributions higher than 10% (see also Gouin et al 2020). In details, the azimuthal matter distribution inside galaxy clusters (up to R 200 ) is almost quadrupolar, whereas the matter distribution in cluster infalling regions (from R 200 to 4 × R 200 ) is mainly traced by the harmonic orders m = 1, 2, 3, 4.…”
Section: Appendix A: Multipolar Expansion Of Dm Distributionmentioning
confidence: 90%
“…with |Q m | the modulus of the aperture multipole moment at the order m. By decomposing surface mass density in harmonic expansion terms, Schneider & Weiss (1991) have shown that |Qm| |Q0| −→ 1/2 for a matter distribution Σ(θ) ∝ cos(2θm). Therefore, the value of multipolar ratio β m varies between 0 and 1/2, such that β m = 0 for a circular matter distribution and β m = 1/2 for a matter distribution describing the azimuthal symmetry at the order m (see also Vallés-Pérez et al 2020, for a similar definition).…”
Section: Formalism Of Multipole Moments Q Mmentioning
confidence: 99%
“…The simulation analysed in this paper has been carried out with the cosmological code MASCLET [42], and has been already employed in a series of previous works [43,44,45]. Here we shall introduce the main details of the simulation, while some topics which are not intimately connected to the analyses in this paper can be found in more detail in the aforementioned references.…”
Section: Simulation Detailsmentioning
confidence: 99%
“…This same object has been analysed in great detail in[44] (focusing on its observational properties) and[45] (exploring its accretion history).…”
mentioning
confidence: 99%
“…The inner slope of the mass distribution might deviate from the NFW model because of several processes such as dynamical friction, central condensation of cooled gas, and active galactic nucleus (AGN) feedback (e.g., Blumenthal et al 1986;Martizzi et al 2012;Schaller et al 2015;Laporte & White 2015;Peirani et al 2017;He et al 2020). The external slope of the mass distribution in individual clusters might deviate from the NFW model depending on the mass accretion rate in the cluster outskirts (e.g., Diemer & Kravtsov 2014;More et al 2015;Vallés-Pérez et al 2020). The shape of the cluster mass profile also depends on the properties of the dark matter (DM) component.…”
Section: Introductionmentioning
confidence: 99%